2018
DOI: 10.1016/j.tvjl.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of oral and parenteral cobalamin supplementation in normalising low cobalamin concentrations in dogs: A randomised controlled study

Abstract: The aim of this study was to compare the efficacies of parenteral and oral cobalamin supplementation protocols in dogs with chronic enteropathies and low cobalamin concentrations. It was hypothesised that both treatments would increase serum cobalamin concentrations significantly. Fifty-three dogs with chronic enteropathies and serum cobalamin concentrations<285ng/L (reference interval 244-959ng/L) were enrolled. Dogs were randomised to treatment with either daily oral cobalamin tablets (0.25-1.0mg cyanocobala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(73 citation statements)
references
References 31 publications
2
64
3
4
Order By: Relevance
“…However, hypocobalaminemia is not specific for CIE and also can be observed in dogs with exocrine pancreatic insufficiency 31. Also, a normal serum cobalamin concentration does not rule out a diagnosis of CIE. Subnormal or low normal serum cobalamin concentrations (<400 ng/L) indicate a need for parenteral (50 μg/kg SQ once weekly for 6 weeks, then every 2‐4 weeks) or PO supplementation (50 μg/kg PO q24h for at least 12 weeks) with cyanocobalamin 51, 52…”
Section: Biomarkers In Chronic Inflammatory Enteropathies Of Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, hypocobalaminemia is not specific for CIE and also can be observed in dogs with exocrine pancreatic insufficiency 31. Also, a normal serum cobalamin concentration does not rule out a diagnosis of CIE. Subnormal or low normal serum cobalamin concentrations (<400 ng/L) indicate a need for parenteral (50 μg/kg SQ once weekly for 6 weeks, then every 2‐4 weeks) or PO supplementation (50 μg/kg PO q24h for at least 12 weeks) with cyanocobalamin 51, 52…”
Section: Biomarkers In Chronic Inflammatory Enteropathies Of Dogsmentioning
confidence: 99%
“…Hypocobalaminemia is a negative prognostic factor in dogs with CIE and is associated with hypoalbuminemia. 5,9 However, hypocobalaminemia is not specific for CIE and also can be 51,52 Methylmalonic acid (MMA) is a metabolite that accumulates when the activity of methylmalonyl-CoA mutase is decreased because of a lack of intracellular cobalamin. 53 Thus, increased MMA production is a useful marker for cobalamin deficiency at the cellular level as a result of cobalamin malabsorption, decreased cobalamin transport, or both.…”
Section: Fecal and Serum Alpha 1 -Proteinase Inhibitor (α 1 Pi)mentioning
confidence: 99%
“…This requires frequent visits to veterinary clinics, can be distressing for both owners and dogs, and costly. Toresson et al, (2018) found that one dog was hypocobalaminaemic (38 ng/L) at day 90 after following this parenteral protocol. This suggests that the parenteral protocol was not adequate at supplementing cobalamin in this case.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 91%
“…Toresson et al (2016) produced a retrospective study based on a review of medical records of dogs that had been treated with oral cobalamin; the study concluded that dogs treated with oral cobalamin had normal cobalamin blood serum levels (>270 ng/L). A randomised clinical trial was later performed by Toresson et al (2018). This experimental trial concluded that both oral and parenteral cobalamin supplementation in dogs provided a significant increase in serum cobalamin concentrations >285 ng/L.…”
Section: The Evidencementioning
confidence: 99%
See 1 more Smart Citation